(3MSH GdfXGe GdeMGSHj GdeGdj s - (3fHjd(B, (3HhadjMs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2019)
(3jSJYQV GdcJGH Cge GdCSS hGdbhGYO hGdJbfjGJ GdeYJeOI aj GdJMdjd GdeGdj dGSjeG aj Xd GdJWhQGJ GdJj TgOgG GdejOGf GdeGdj hGdeMGSHj HYO GYJeGO fXGe eMGSHj LOjO efP SfI (B2010(3, hgh ehLg dWdHI ejOGf GdYdhe GdGbJUGOjI hGdJLGQjI hYdhe GdJSjjQ HGdGVGaI Gdi GdYGedjf aj ejOGf GdeGdjI hGdeMGSHI aj eNJda GdTQcGJ GdGbJUGOjI hGdeDSSGJ GdeGdjI, ceG jJejR GdcGJH HhLhO JQGHW hJcGed Hjf GdLGfHjf GdfXQj hGdJWHjbj Yf WQjb JOYje LejY GdaUhd HCeKdI hMGdGJ JWHjbjI eQabI eY Mdhd fehPLjI eGjVef ddbGQF JMce Yedj HCge WQb GdJMdjd GdeGdj hjecfg ef eeGQSI eNJda GdegGe GdeQJHWI HhXjaI GdJSjjQ GdeGdj aj GdeDSSI(B.s
(3eQGLY U(B.159 (3bGFeI Cge GdeUWdMGJ GdeSJNOeI aj GdJMdjd GdeGdj U(B.161s
Keywords: (3GdfXGe GdeMGSHj GdeGdj (B- (3GdLRGFQs; (3GdJMdjd GdeGdjs